Manual de funciones para mejorar la gestión administrativa de la gasolinera “San José” del cantón Quevedo, año 2012 - Barragán Álvarez, Lorena Rosalba (2013)
This research was conducted at the Gas Company "San Jose" Quevedo Canton, is a company dedicated to the sale of fuel. The Gas station "San Jose" is located in the province of Los Ríos, Quevedo Canton, St. Charles Parish, Precinct The Banana, located at Km 23 Via Quevedo - Windows, in the city has about 10 years of providing this service, Mr. Ing Ligner Fernández Muñoz holds the position of General Manager. In a meeting with the Manager of the Company, was found several negative aspects that were being presented by the lack of jobs, not having a manual functions, these could highlight, assigning responsibilities without capacity to perform, waste of time to provide solutions to situations that would otherwise have to be analyzed, evaluated and resolved by the employee responsible whenever they arise, in addition to not be clear what their roles and daily, all staff performs the same functions. Analysis was made to the current situation of the company Petrol station "San Jose" Quevedo Cantón, to identify existing problems, this information is presented in the results by their respective figures tabulation and analysis then identified the areas that make the organizational structure of the Company, for which we developed a flow chart of the same. An analysis and job description information that helped the design manual specified functions where activities and responsibilities in each of the charges as well as the processes taking place in the company resulting from the most relevant interview conducted with collaborators Gas Company "San Jose", it is discovered that there is a majority who know their roles within that organization, 60% of employees are overworked because activities do not correspond to his office, because that there is no division of responsibilities in the activities that take place in office, 40% of employees have never received administrative induction course, considering that there are established roles and responsibilities are not outlined its descriptive function, the research provides Conceso result in general the existence of manual functions that allow optimizing human resources and optimize the service within the Company. The manual is a valuable tool functions of business management, which allows employees at different hierarchical levels of the organizational structure are clear and full knowledge of its functional competence and responsibility at each job.